Prevalensi Penderita Diabetes Melitus Tipe-II pada Pasien di Puskesmas Kota Blangkejeren, Kecamatan Blangkejeren, Kabupaten Gayo Lues Tahun 2015 – 2017 - Sabarinah Sabarinah; Ida Fauziah; Dewi Nur Anggraeni (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
Type-II Diabetes Mellitus is a metabolic disorder which characterised by the increase of blood glucose level (hypergliycemia). The purpose of this study was to determine the prevalence of type-II Diabetes Mellitus in the Puskesmas of Blangkejeren, Gayo Lues District in 2015-2017 and to investigate the patient lifestyle. The research was conducted is descriptive method by colleting data from patient medical record and the result showed that the prevalence of type-II Diabetes Mellitus in 2015-2017 is 16,2 %, the patients were dominated by female and those in the age of 40-49. Most of patients found to have higher daily sugar intake